A case study of a family with a boy with PACS1 syndrome through the PICCOLO scale - Teira Serrano, Celia; Martínez Castilla, Pastora; Nieto , Carmen (Revista de Investigación en Logopedia, 2024)
Family-Centered Models for Early Intervention enhance not only family empowerment but also child’s greater competence in daily routines. Our work follows this model and presents a single case intervention study with the family of a child with PACS1 syndrome, a neurodevelopmental disorder of genetic origin and with a very low prevalence. The study took place for a year and analyzed monthly recordings of the father playing with his son by using PICCOLO, a Parenting Interaction Scale. We stablished a baseline of PICCOLO scores for three months, and, afterwards, we gathered through videoconference with the family every two months to give them feedback about their concerns and in order to present them with the different intervention goals. Goals were related to specific aspects in each of the 4 domains of the scale, to facilitate their understanding of the development and interactions with the child. The father was in the average for scores on the four domains, and he evolved positively and constantly in one aspect (item 3 of the Teaching scale: “Repeat or expand the words or sounds of the child"). At the end, this way of intervention was evaluated with the family, they highlighted the usefulness of seeing the recordings afterwards and their feeling of competence.